Causes of variable reproductive performance by Southern Ground‐hornbill Bucorvus leadbeateri and implications for management. (2nd April 2013) - Wilson, Gwyneth; Hockey, Philip A. R.; Marsden, Stuart
<x xml:space="preserve">Abstract</x> Range occupancy of the cooperatively breeding Southern Ground‐Hornbill Bucorvus leadbeateri in South Africa has decreased by 65% in the last three generations and the effective management of the remaining populations is hampered by a lack of fundamental understanding of the factors determining reproductive performance. We examined the influence of social and environmental factors on the species' reproductive success in South Africa using data gathered from 23 groups over eight breeding seasons. Some groups had access to artificial nest‐sites, others did not. High rainfall (> 500 mm) over the breeding season led to a decrease in reproductive success, with groups being most successful in years when rain in the vicinity of the nest ranged from 300 to 500 mm. Groups breeding in natural nests were successful only when the proportion of open woodland surrounding the nest‐site was high. Those that bred in artificial nests, where overall breeding success was more than twice as high as those in natural nests, were less dependent on the availability of open woodland. Large groups (more than three birds) bred more successfully than groups comprising only two to three individuals. Group size, helper effects and rainfall cannot be managed to increase the productivity of Ground‐Hornbills but the fact that the availability of artificial nest‐sites and the amount of open woodland around the nest‐site both contribute positively to breeding performance identifies practical and simple management options for increasing the reproductive output of Southern Ground‐Hornbill populations.